The Collective Corridor-Shaped Tombs of The Daba Al Bayaah Necropolis (Musandam, Oman): The Origin and Spread of A Funerary Structure Based On Evidence From South-East Arabia - Genchi, Francesco (The Journal of Oman Studies, 2025)
This paper takes as its starting point the exploration of two collective tombs of the corridor-shaped type, also known as ‘long-chambered’, identified in the 2nd/1st millennium BC necropolis at Daba Al Bayaah, on the east coast of the Musandam Peninsula in the Sultanate of Oman. The spread of this type of tomb is limited to the northern region of the Oman Peninsula, and to the period between the middle/late Bronze Age and the beginning of the Iron Age (first half of the 2nd millennium BC - first half of the 1st millennium BC). These tombs are of monumental character with a corridor chamber, usually semi-subterranean, that can reach a length of up to 30 m. The focus is therefore on the diffusion confined to the northern area of south-eastern Arabia, comparing the investigated specimens, and describing similarities and differences in order to hypothesise construction patterns. Furthermore, light is shed on the origins of this phenomenon, which are probably to be found in Iranian Luristan, on the basis of some similar architectural choices linked to funerary aspects and on the presence of objects of clear Iranian derivation among Dibbā findings.